Preparation and Characterization of Paromomycin Encapsulated in Lecithin-chitosan Nanoparticles for the Topical Treatment of Cutaneous Leishmaniasis - Zamanpour, Maryam; Arjmand, Reza; Saki, Jasem; Bavarsad, Neda; Jelowdar, Ali (Current Analytical Chemistry, 2025)
IntroductionLeishmaniasis is a disease caused by the Leishmania protozoa, with Cutaneous Leishmaniasis (CL) being the most common form of the illness. Paromomycin (PM) has recently garnered increased interest for its effectiveness against Leishmania, but it is hindered by limited efficacy, low oral bioavailability, and rapid clearance. As far as we know, there have been no studies examining the impact of nano lecithin-chitosan-containing paromomycin (Nano-PM) on CL. Therefore, the objective of the present study was to create Nano-PM and assess its effects on the promastigotes in vitro and on the lesions caused by Leishmania major in the BALB/c mice model in vivo.MethodsThe loading of PM into lecithin-chitosan nanoparticles was achieved using the ionic gelation method, and the resulting nanoparticles were characterized. The IC50 values for PM, Glucantim, and Nano-PM against promastigotes were determined after 24, 48, and 72 hours of treatment. The viability of promastigotes was assessed using the MTT assay. The Nano-PM formulation was administered local treatment to mice for a period of 28 days, during which lesion sizes were measured weekly. Furthermore, the parasite load in the infected mice was quantified using quantitative real-time polymerase chain reaction (qPCR).ResultsIC50 of Nano-PM was significantly lower than Glucantim (p < 0.0001 after24 h incubation, p = 0.013 for 48h and p < 0.0001 for 72 h) and PM (p < 0.0001 after24 h, p = 0.003 for 48h and p < 0.0001 for 72h). All concentrations of Nano-PM had the highest toxicity on promastigotes in comparison with other groups after 24, 48, and 72 h treatment. Moreover, a significant reduction in the lesion size was found in the Nano-PM group in comparison with the control group after three (p = 0.0369) and four (p = 0.0009) weeks of treatment. More importantly, Nano-PM significantly reduced the parasite load compared to the control and the lecithin-chitosan groups (p = 0.001 for both).ConclusionOur findings showed that Nano-PM had lower toxicity (lower IC50) on promastigotes compared to Glucantim and PM. Moreover, Nano-PM treated mice showed reduced lesion size compared to the control group. Additionally, Nano-PM led to a significant decrease in parasite burden compared to the control group and the lecithin-chitosan group. Nevertheless, more complementary research is needed to approve our findings.
Keywords: paromomycin